An investigation of the comparability of commercially sourced plasma and pharmaceutical study plasma, using total protein concentration. (February 2016) - Felgate, Clive; Spooner, Neil; Calloway, Robert
Background: Control blood plasma is regularly used in bioanalysis, biomarkers and proteomics, and is often obtained from commercial sources. It has always been assumed that this plasma will be comparable to plasma drawn during a drug development study.Results: When compared using total protein concentrations, plasma from only one species (dog) demonstrated statistical comparability, plasma from all other species tested (human, rabbit, mouse and rat) shows a statistically significant difference.Conclusion: If endogenous components of blood plasma are being measured, or if an assay technique does not significantly limit matrix effects, any assay controls should be prepared using control plasma from the drug development site, or using commercial plasma that has been screened against drug development site plasma.